Proof of heaven : a neurosurgeon's journey into the afterlife - Alexander, Eben. (New York : Simon & Schuster, 2012)
"A SCIENTIST'S CASE FOR THE AFTERLIFE Near-death experiences, or NDEs, are controversial. Thousands of people have had them, but many in the scientific community have argued that they are impossible. Dr. Eben Alexander was one of those people. A highly trained neurosurgeon who had operated on thousands of brains in the course of his career, Alexander knew that what people of faith call the "soul" is really a product of brain chemistry. NDEs, he would have been the first to explain, might feel real to the people having them, but in truth they are simply fantasies produced by brains under extreme stress. Then came the day when Dr. Alexander's own brain was attacked by an extremely rare illness. The part of the brain that controls thought and emotion--and in essence makes us human-- shut down completely. For seven days Alexander lay in a hospital bed in a deep coma. Then, as his doctors weighed the possibility of stopping treatment, Alexander's eyes popped open. He had come back. Alexander's recovery is by all accounts a medical miracle. But the real miracle of his story lies elsewhere. While his body lay in coma, Alexander journeyed beyond this world and encountered an angelic being who guided him into the deepest realms of super-physical existence. There he met, and spoke with, the Divine source of the universe itself. This story sounds like the wild and wonderful imaginings of a skilled fantasy writer. But it is not fantasy. Before Alexander underwent his journey, he could not reconcile his knowledge of neuroscience with any belief in heaven, God, or the soul. That difficulty with belief created an empty space that no professional triumph could erase. Today he is a doctor who believes that true health can be achieved only when we realize that God and the soul are real and that death is not the end of personal existence but only a transition. This story would be remarkable no matter who it happened to. That it happened to Dr. Alexander makes it revolutionary. No scientist or person of faith will be able to ignore it. Reading it will change your life"--
"Near-death experiences are controversial. Thousands of people have had them, but many in the scientific community have argued that they are impossible. Dr. Eben Alexander was one of those people. A highly trained neurosurgeon, Alexander knew that what people of faith call the "soul" is really a product of brain chemistry. NDEs, he would have been the first to explain, might feel real, but they are fantasies produced by brains under extreme stress. Then came the day when Dr. Alexander's own brain was attacked by a rare illness. The part of the brain that controls thought and emotion--and in essence makes us human--shut down completely. For seven days Alexander lay in a hospital bed in a deep coma. Then, as his doctors weighed the possibility of stopping treatment, Alexander's eyes popped open. He had come back. Alexander's recovery is a medical miracle. But the real miracle of his story lies elsewhere. While his body lay in coma, Alexander journeyed beyond this world and encountered an angelic being who guided him into the deepest realms of super-physical existence. There he met, and spoke with, the Divine source of the universe itself. This story sounds like the wild imaginings of a skilled fantasy writer. But it is not fantasy. Before Alexander underwent his journey, he could not reconcile his knowledge of neuroscience with any belief in heaven, God, or the soul. That difficulty with belief created an empty space that no professional triumph could erase. Today he is a doctor who believes that true health can be achieved only when we realize that God and the soul are real and that death is not the end of personal existence but only a transition. This story would be remarkable no matter who it happened to. That it happened to Dr. Alexander makes it revolutionary"--
Includes bibliographical references (pages 177-182) and index.
Keywords: Alexander, Eben; Near-death experiences -- United States; Neurosurgeons -- United States -- Biography; MEDICAL / General; RELIGION / Eschatology; RELIGION / Religion & Science; Print books